Comparative Analysis Of The Factors Affecting The Performance Of Spbe Implementation In The City Of Surabaya And Mojokerto Regency - Anggito Hernando; Indri Sudanawati Rozas; Anang Kunaefi (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The implementation of e-government in Indonesia in 2018 changed its name to the Electronic-Based Government System (SPBE) in accordance with the PERPRES No. 95 of 2018. The implementation of SPBE in Indonesia in 2019 an evaluation was held in each region to find out the extent of the implementation of SPBE in each region in Indonesia. The SPBE evaluation produces an SPBE index which is used as a reference in knowing how far the implementation of the existing SPBE in the area. The high and low value of the SPBE index can be caused by various factors, in this study will discuss the comparison of factors and model factors that affect the performance of the SPBE application in the City of Surabaya and Mojokerto Regency. This study uses EFA analysis to determine the performance factor model in the application of SPBE. For the variables in this study using the results of mapping the Digital Service Provision System of System Framework by Samantha Papavasilou with PERMENPAN No. 59 of 2020 which resulted in 17 indicators. The results of this study Surabaya City and Mojokerto Regency have similarities in performance factors but the two regions have differences in performance factor characteristics where there are several performance factors that are superior to Surabaya City than Mojokerto Regency and vice versa. For the performance factor model, the EFA analysis produces 5 performance factors, namely SPBE regulation, digital literacy, IT infrastructure management, Human Resources and system location.